Embedded AI Ethics and Right in Civic Education in Nigerian Secondary Schools. Measuring Efficacy and Psychological Engagement - Ogbu, Eke Eke; Chukwu , Chukwuma Ogbonnaya; Chukwudebelu , Chinwe Bright; Onyekwere , Nonye Adanma; Ibebuike, Ursula Obiageli; Azubuike, Ogechi J. (RESEARCH TRENDS IN HUMANITIES Education & Philosophy, 2026)
This study investigates the integration of artificial intelligence (AI) ethics and rights into civic education within Nigerian secondary schools, focusing on curriculum relevance, psychological engagement, and implementation challenges. The research addresses a critical gap in the literature, as AI ethics remains largely absent from the civic education curriculum despite the increasing influence of digital technologies on governance and civic life. The study employed a descriptive research design using mixed methods, combining quantitative surveys from 300 students and qualitative interviews with 30 teachers and 10 school administrators from public secondary schools in Calabar and Owerri. Data collection tools included a structured questionnaire assessing students’ awareness, perception, and engagement with AI ethics, and semi-structured interviews exploring curriculum integration and institutional support. Findings reveal minimal integration of AI ethics in the curriculum, with only 33.3% of schools reporting any inclusion in syllabi and 10% indicating teacher training. Students demonstrated high perceived relevance but moderate understanding and psychological engagement. Teachers identified institutional barriers including lack of training, curriculum materials, and infrastructure. Despite these challenges, there was strong support for integrating AI ethics to enhance digital citizenship and critical thinking. The study underscores the need for curriculum reform, teacher development, and policy alignment to prepare students for ethical participation in a digital society.